Perplexity AI for Academic Writing Development: Findings from EFL Students at Muhammadiyah University of Mataram - Zikrina Hidayati; Ilham; Rima Rahmaniah (Universitas Cokroaminoto Palopo, 2026)
This study investigates the effectiveness of Perplexity AI as a learning tool to enhance academic writing skills among Indonesian EFL university students at Muhammadiyah Mataram, NTB. Employing a mixed-methods design, the study combined quantitative and qualitative approaches. Quantitative data were collected through pre-test and post-test writing assessments and a perception survey, while qualitative data were obtained from open-ended questionnaires. The findings reveal a significant improvement in students’ academic writing performance after the integration of Perplexity AI. The mean score increased from 64.92 (pre-test) to 82.08 (post-test). Statistical analysis using the Wilcoxon test indicated a significant difference between the two scores (Sig. < 0.001), confirming the effectiveness of the intervention. Qualitative results further indicate that students perceived Perplexity AI as a helpful tool in organizing ideas, improving coherence, and developing more academically structured paragraphs. In conclusion, the use of AI, particularly Perplexity AI, demonstrates strong potential in supporting EFL students’ academic writing development. These findings contribute to the growing body of research on AI-assisted language learning and highlight its practical implications in higher education contexts.